2001
DOI: 10.2307/3237003
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and succession of epiphytic macrolichen communities in low‐elevation managed conifer forests in Western Oregon

Abstract: Abstract. We examined epiphytic macrolichen communities in Pseudotsuga menziesii (Douglas‐fir) forests across the western Oregon landscape for relationships to environmental gradients, stand age and structure, and commercial thinning. We used a retrospective, blocked design through the Coast and the western Cascade ranges of Oregon. Each of our 17 blocks consisted of a young, unthinned stand (age 50–110 yr); an adjacent, thinned stand of equivalent age; and an old‐growth stand (age > 200 yr). We found 110 epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
63
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 49 publications
(60 reference statements)
9
63
0
1
Order By: Relevance
“…The number of lichen species was in the same range as those observed in other European forests: e.g., in Italy (Giordani, 2007), Slovenia (Poličnik et al, 2008), or Portugal (Pinho et al, 2004); the Shannon index, however, showed higher values compared to other European and North American forested sites (Mulligan, 2009;Peterson and McCune, 2001). But, this range was higher than in boreal environments (Kuusinen, 1996), probably in relation to specific climate conditions in cold regions.…”
Section: Lichen Diversity and Communitiessupporting
confidence: 59%
“…The number of lichen species was in the same range as those observed in other European forests: e.g., in Italy (Giordani, 2007), Slovenia (Poličnik et al, 2008), or Portugal (Pinho et al, 2004); the Shannon index, however, showed higher values compared to other European and North American forested sites (Mulligan, 2009;Peterson and McCune, 2001). But, this range was higher than in boreal environments (Kuusinen, 1996), probably in relation to specific climate conditions in cold regions.…”
Section: Lichen Diversity and Communitiessupporting
confidence: 59%
“…However, data are still lacking on which to base the management of both biological conservation and timber production in plantations. Some researchers have recommended long-rotation plantations as one source of such data [12,19,36,37,41]. Long-rotation plantations have been found to maintain and restore species diversity and stand structure, important factors for wildlife and plant habitat, to a greater extent than standard-rotation plantations [7,14,19,27].…”
Section: Introductionmentioning
confidence: 99%
“…En revanche, la maturité n'influence pas la diversité des macrolichens épiphytes. Ce groupe d'espèces àc roissance lente est pourtant bien connu pour sa dépendance aux très gros arbres (Peterson et McCune, 2001). Cette absence d'effet de la maturité sur les macrolichens épiphytes est sans doute liée àl ag estion par coupe sélectivep ratiquée en forêts de montagne, qui permet àl 'échelle du peuplement le maintien d'une «bonne »q ualité d'habitat globale.…”
Section: Discussionunclassified